Acute Changes in Creatine Kinase Serum Levels in Adults Submitted a Static Stretching and Maximal Strength Test - M.G. Bara Filho; J.R. Lima; E.H. Dantas; F.J. Aidar; E.P. César (Desafio Singular, 2008)
Strength and flexibility are common components of a training program and their maximal values are obtained through specific tests. However, little information about the damage effect of these training procedures in a skeletal muscle is known. Objective: To verify a serum CK changes 24 h after a sub maximal stretching routine and after the static flexibility and maximal strength tests. Methods: the sample was composed by 14 subjects (man and women, 28 ± 6 yr.) physical education students. The volunteers were divided in a control group (CG) and experimental group (EG) that was submitted in a stretching routine (EG-ST), in a maximal flexibility static test (EG-FLEX) and in 1-RM test (EG-1-RM), with one week interval among tests. The anthropometrics characteristics were obtained by digital scale with stadiometer (Filizola, São Paulo, Brasil, 2002). The blood samples were obtained using the IFCC method with reference values 26-155 U/L. The De Lorme and Watkins technique was used to access maximal maximal strength through bench press and leg press. The maximal flexibility test consisted in three 20 seconds sets until the point of maximal discomfort. The stretching was done in normal movement amplitude during 6 secons. Results: The basal and post 24 h CK values in CG and EG (ST; Flex and 1 RM) were respectively 195,0 ± 129,5 vs. 202,1 ± 124,2; 213,3 ± 133,2 vs. 174,7 ± 115,8; 213,3 ± 133,2 vs. 226,6 ± 126,7 e 213,3 ± 133,2 vs. 275,9 ± 157,2. It was only observed a significant difference (p = 0,02) in the pre and post values inGE-1RM. Conclusion: only maximal strength dynamic exercise was capable to cause skeletal muscle damage.